Singapore’s Anopheles sinensis Form A is susceptible to Plasmodium vivax isolates from the western Thailand–Myanmar border - Pang, Sook-Cheng (Malar J, 2017)
BACKGROUND: Singapore has been certified malaria-free by the World Health Organization since November 1982. However, sporadic autochthonous malaria outbreaks do occur. In one of the most recent outbreaks of vivax malaria, an entomological investigation identified Anopheles sinensis as the most probable vector. As metaphase karyotype studies divided An. sinensis into two forms, A and B, with different vector competence: the investigation of vector competence of An. sinensis found in Singapore was thus pursued using Plasmodium vivax field isolates from the Thailand–Myanmar border. METHODS: Adults and larvae An. sinensis were collected from Singapore from 14 different locations, using various trapping and collection methods between September 2013 and January 2016. Molecular identification of An. sinensis species were conducted by amplifying the ITS2 and CO1 region using PCR. Experimental infections of An. sinensis using blood from seven patients infected with P. vivax from the Thailand–Myanmar border were conducted with Anopheles cracens (An. dirus B) as control. RESULTS: Phylogenetic analysis showed that An. sinensis (F(22), F(2) and collected from outbreak areas) found in Singapore was entirely Form A, and closely related to An. sinensis Form A from Thailand. Artificial infection of these Singapore strain An. sinensis Form A resulted in the development of oocysts in four experiments, with the number of sporozoites produced by one An. sinensis ranging from 4301 to 14,538. CONCLUSIONS: Infection experiments showed that An. sinensis Form A from Singapore was susceptible to Thai–Myanmar P. vivax strain, suggesting a potential role as a malaria vector in Singapore.